A theoretical study on the molecular encapsulation of luteolin and pinocembrin with various derivatized beta-cyclodextrins - Panupong Mahalapbutr (2019)
© 2018 Elsevier B.V. Luteolin (LL) and pinocembrin (PB) are plant-derived flavonoids predominantly found in many fruits and vegetables showing several biological effects, especially an antioxidant activity. However, the low water solubility of these two compounds limits their use in many pharmaceutical applications. Beta-cyclodextrin (βCD) and its derivatives (e.g., methylated (M) and hydroxypropylated (HP) βCDs) have been extensively used to enhance the stability and solubility of many hydrophobic guest molecules through an encapsulation process into the lipophilic inner cavity. In the present study, the dynamics behavior and the stability of inclusion complexes of two flavonoids LL and PB with βCDs were studied using all-atom molecular dynamics simulations and MM/PB(GB)SA free energy calculations. The obtained results showed that the van der Waals driven encapsulation of LL and PB could adapt the structure of the βCDs to become more stable conformers via an enhanced intramolecular hydrogen bond formation on the secondary rim. The structural data and free energy results demonstrated that the phenyl orientation was the preferred binding mode for LL and PB inclusion complexations. In addition, βCD derivatives, especially HPβCDs, could significantly enhance the stability of both flavonoids better than natural βCD.